Recent Advances on Mg–Li–Al Systems for Solid-State Hydrogen Storage: A Review - Sazelee, Noratiqah; Ali, Nurul Amirah; Yahya, Muhammad Syarifuddin; Mustafa, Nurul Shafikah; Halim Yap, Firdaus Abdul; Mohamed, Saiful Bahri; Ghazali, Muhammad Zahruddin; Suwarno, Suwarno; Ismail, Mohammad (Frontiers in Energy Research, 2022)
The problem of providing compact and safe storage solutions for hydrogen in solid-state materials is demanding and challenging. The storage solutions for hydrogen required high-capacity storage technologies, which preferably operate at low pressures and have good performances in the kinetics of absorption/desorption. Metal hydrides such as magnesium hydride (MgH2) are promising for such storage solutions, but several drawbacks including high onset desorption temperature (>400°C) and slow sorption kinetics need to be overcome. In this study, we reviewed the recent developments in hydrogen storage performance development of MgH2 and found that the destabilization concept has been extensively explored. Lithium alanate or LiAlH4 has been used as a destabilizing agent in the MgH2–LiAlH4 (Mg–Li–Al) due to its high capacity of hydrogen, which is 10.5 wt.%, and low onset desorption temperature ( 150°C). In this paper, a review on the recent advances in the Mg–Li–Al system for solid-state hydrogen storage material is studied. We discussed the effect of the ratio of MgH2 and LiAlH4, milling time and an additives in the Mg–Li–Al system. After the destabilization concept was introduced, the onset of desorption temperature and activation energy of MgH2 were reduced and sorption properties improved. Further study showed that the intermetallic alloys of Li0.92Mg4.08 and Mg17Al12 that were formed in situ during the dehydrogenation process provide synergetic thermodynamic and kinetic destabilization in the Mg–Li–Al composite system. De/rehydrogenation measurements indicate that the intermetallic alloys Li0.92Mg4.08 and Mg17Al12 were fully reversible absorbed and desorbed hydrogen. Next, the remaining challenges and a possible development strategy of the Mg–Li–Al system are analyzed. This review is the first systematic study that focuses on recent advances in the Mg–Li–Al system for storage solutions for hydrogen in solid-state materials.